Supporting the Development and Learning of Children through Personal and Professional Development of Staff - Catriona McDonald (University of Aberdeen, School of Education, 2017)
Current Scottish Government policy, A Blueprint for 2020: The Expansion of Early Learning and Childcare in Scotland, (2017), acknowledges that the skillset for this workforce differs from that required for working with older children and that quality provision for young children requires the support of well qualified staff. In the years since publication of the initial Scottish Government policy (2008) it appears that the sector still suffers from inconsistencies in pay and conditions, necessary qualifications and opportunities for career progression.